Designing Games, Designing Roles: A Study of Youth Agency in an Urban Informal Education Program. (September 2013) - Sheridan, Kimberly M.; Clark, Kevin; Williams, Asia
Collaboration (GDMC), an informal education program in 3D computer modeling and 2D interactive game design serving primarily African American youth aged 7 to 19 years in the Washington, D.C. metro area, transformed from a program designed and taught by adults to one designed and taught by youth. In Year 1, 8% of youth participants held a leadership role; by Year 4, 30% of youth participants did. Moreover, the nature of these roles transformed, with youth increasingly taking on responsibilities formerly held by adults. In this qualitative study, the authors describe and seek to understand this role shifting. Through the extensive collection and analysis of field observations over 4 years, the authors describe qualitative shifts in the agency involved in these roles—moving from a conception of youth as student to assistant to youth as designer and implementer of instruction. The authors analyze changes in youth agency that accompanied their implementation of the studio mentorship model where classrooms were transformed from traditional teacher-led classes to studios with a 1:3 ratio of peer mentors to students. The authors describe how, following this shift, youth initiated new instructional roles leading to the creation of a mentor-instructor pipeline. The authors pose the GDMC program as an example to discuss how culturally relevant computing practice emerges from a programmatic goal of viewing youth as assets and actively seeking ways to support youth's initiatives and agency in digital technology education. The authors argue for the value of this asset building in technology education as a way to encourage youth from traditionally underserved groups to become technology leaders and innovators.